Poetical Peculiarities of Satirical Depiction of the Novel “Hard Times” by Ch. Dickens and the Short Story “Zabobon” by Les Martovych (Comparative-Typological Aspect) - Bogachevska, L. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article is devoted to the comparative-typological analysis of the satirical works “Hard times” by Ch. Dickens and “Zabobon” by Les Martovych. This investigation regards different means of satirical depiction such as contrast, hyperbole, characters’ specific manner of speech